A Two-Component Regulatory System, pehR-pehS , Controls Endopolygalacturonase Production and Virulence in the Plant Pathogen Erwinia carotovora subsp. carotovora - Flego, Diana; Marits, Reet; Eriksson, Anders R. B.; Kõiv, Viia; Karlsson, Maj-Brit; Heikinheimo, Riikka; Palva, E. Tapio (Molecular plant-microbe interactions, 2000)
Genes coding for the main virulence determinants of the plant pathogen Erwinia carotovora subsp. carotovora, the plant cell wall-degrading enzymes, are under the coordinate control of global regulator systems including both positive and negative factors. In addition to this global control, some virulence determinants are subject to specific regulation. We have previously shown that mutations in the pehR locus result in reduced virulence and impaired production of one of these enzymes, an endopolygalacturonase (PehA). In contrast, these pehR strains produce essentially wild-type levels of other extracellular enzymes including pectate lyases and cellulases. In this work, we characterized the pehR locus and showed that the DNA sequence is composed of two genes, designated pehR and pehS, present in an operon. Mutations in either pehR or pehS caused a Peh-negative phenotype and resulted in reduced virulence on tobacco seedlings. Complementation experiments indicated that both genes are required for transcriptional activation of the endopolygalacturonase gene, pehA, as well as restoration of virulence. Structural characterization of the pehR-pehS operon demonstrated that the corresponding polypeptides are highly similar to the two-component transcriptional regulators PhoP-PhoQ of both Escherichia coli and Salmonella typhimurium. Functional similarity of PehR-PehS with PhoP-PhoQ of E. coli and S. typhimurium was demonstrated by genetic complementation.